2021
DOI: 10.1111/1759-7714.14112
|View full text |Cite
|
Sign up to set email alerts
|

Use of crizotinib as neoadjuvant therapy for non‐small cell lung cancers patient with ROS1 rearrangement: A case report

Abstract: Crizotinib showed significant antitumor effect in patients with advanced ROS1‐rearranged non‐small cell lung cancers (NSCLC). Most recently, many studies have explored the feasibility and efficacy of target therapy for perioperative application in NSCLC. Here, we describe a female patient who was diagnosed with stage IIIB lung adenocarcinoma exhibiting a CCDC6‐ROS1 rearrangement by high‐throughput sequencing. The tumor and lymph nodes showed durable response after the treatment of crizotinib. Given that a radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Previous clinical trials have already verified the availability of EGFR and ALK inhibitors neoadjuvant targeted therapy in the disease control and pathological downstaging for early-stage NSCLC patients harboring the corresponding mutation, and some case reports also observed that target therapy provided effective radiologic and pathologic response in ALK , RET and ROS1 -positive resectable NSCLC patients ( 3 , 6 , 13 15 ). MET ex14m is an independent oncogenic driver occurring in 2.8% of resected stage I-III NSCLC patients ( 16 ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous clinical trials have already verified the availability of EGFR and ALK inhibitors neoadjuvant targeted therapy in the disease control and pathological downstaging for early-stage NSCLC patients harboring the corresponding mutation, and some case reports also observed that target therapy provided effective radiologic and pathologic response in ALK , RET and ROS1 -positive resectable NSCLC patients ( 3 , 6 , 13 15 ). MET ex14m is an independent oncogenic driver occurring in 2.8% of resected stage I-III NSCLC patients ( 16 ).…”
Section: Discussionmentioning
confidence: 91%
“…Immunohistochemistry outcomes were presented as: HE (A), TTF-1 (+) (B), NapsinA (+) (C), CK7 (+) (D), CK5/6 (-), CK (pan) (+), and Ki-67 (+, about 50%). some case reports also observed that target therapy provided effective radiologic and pathologic response in ALK, RET and ROS1-positive resectable NSCLC patients (3,6,(13)(14)(15). METex14m is an independent oncogenic driver occurring in 2.8% of resected stage I-III NSCLC patients (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pralsetinib was approved by the Food and Drug Administration (FDA) for treating RET fusion-positive NSCLC in 2020. Several studies have verified the availability of neoadjuvant-targeted therapy for NSCLC patients with ROS1, ALK, and epidermal growth factor receptor (EGFR) alterations ( 7 9 ); however, there are no reports regarding pralsetinib as neoadjuvant treatment for NSCLC patients with a RET rearrangement.…”
Section: Introductionmentioning
confidence: 99%
“…In order to give patients the opportunity of undergoing surgery, neoadjuvant chemotherapy has been proposed, particularly in patients with locally advanced NSCLC ( 5 8 ). Notably, in patients with locally advanced NSCLC exhibiting sensitive gene mutations [such as epidermal growth factor receptor (EGFR), anaplastic lymphoma kinase (ALK) and proto-oncogene tyrosine-protein kinase ROS (ROS1) alterations], the addition of a tyrosine kinase inhibitor to chemotherapy as the neoadjuvant regimen could further improve the patient prognosis; however, in patients without sensitive gene alterations, these novel drugs are not applicable ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%